PENYEBAB KEGAGALAN PENGENTASAN MASALAH PEKERJA ANAK DI TAMBANG MIKA JHARKHAND INDIA - Dewi, Anak Agung Anik Kristina; Kumala Dewi, Putu Ratih; Kurnia Putri, Penny (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL); Vol 2 No 1 (2022): Jurnal DIKSHI, 2022)
This research aims to understand the causes of the failure of alleviating the child labor problem in the Jharkhand mica mines even though there are significant measures that have been taken by the parties that involved in the Jharkhand mica mining. Therefore, this draws upon dependency theory , the MNC concept, and the poverty traps concept. This research finds that the failure of alleviating the problem of child labor in Jharkhand India's mica mines are caused by conditions of constant poverty and Jharkhand's dependence on extractive industries in a world system that positions Jharkhand as a “peripheral country”. The dynamics of the situation are a potential obstacle to the elimination of child labor in India's Jharkhand mica mines. In addition, new actor such as MNC have appeared as parties to maintain the situation.